Certification of Testing Laboratories – The Basis of Reliability Among Research Vendors in Aviation - Wichniarz Marzena (Fatigue of Aircraft Structures, 2021)
Material characterization and assessment is a crucial stage in most of aviation and aeronautical research and a basis for further design and testing of more complex aircraft elements and structures. Material test’s reliability can only be guaranteed by conducting them at independent and reliable laboratories, operating based on a management system assessed by a third-party such as the accreditation according to the ISO / IEC 17025 or NADCAP or having the qualification of the second-party based on specific customer requirements. This paper introduces basic requirements for material testing laboratories according to accreditation systems and describes its responsibilities as qualified and reliable testing suppliers.